Remote ischemic preconditioning in the prevention of ischemic brain damage during intracranial aneurysm treatment (RIPAT): study protocol for a randomized controlled trial. Issue 1 (December 2015) - Tülü, Selma; Mulino, Miriam; Pinggera, Daniel; Luger, Markus; Würtinger, Philipp; Grams, Astrid; Bodner, Thomas; Beer, Ronny; Helbok, Raimund; Matteucci-Gothe, Raffaella; Unterhofer, Claudia; Gizewski, Elke; et al.
Abstract Background The treatment of intracranial aneurysms may be associated with cerebral ischemia. We hypothesize that pre-interventional remote ischemic preconditioning (RIPC) reduces ischemic cerebral tissue damage in patients undergoing elective intracranial aneurysm treatment. Methods/Design This study is a single-center, prospective, randomized, double-blind explorative trial. Patients with an unruptured intracranial aneurysm admitted to Innsbruck Medical University Hospital for coiling or clipping will be consecutively randomized to either the intervention group (= RIPC by inflating an upper extremity blood-pressure cuff for 3 x 5 min to 200 mmHg) or the control group after induction of anesthesia. Participants will be randomized 1:1 to either the preconditioning group or the sham group using a random allocation sequence and block randomization. The precalculated sample size isn  = 24 per group. The primary endpoint is the area-under-the-curve concentration of serum biomarkers (S100B, NSE, GFAP, MMP9, MBP, and cellular microparticles) in the first five days after treatment. Secondary endpoints are the number and volume of new ischemic lesions in magnetic resonance imaging and clinical outcome evaluated with the National Institutes of Health Stroke Scale, the modified Rankin Scale, and neuropsychological tests at six and twelve months. All outcome variables will be determined by observers blinded to group allocation. This study was approved by the local institutional Ethics Committee (UN5164), version 3.0 of the study protocol, dated 20 October 2013. Discussion This study uses the elective treatment of intracranial aneurysms as a paradigmatic situation to explore the neuroprotective effects of RIPC. If effects are demonstrable in this pilot trial, a larger, prospective phase III trial will be considered.